Implementation of the Human Papillomavirus (HPV) Vaccination Program to Enhance Primary Prevention of Cervical Cancer among the Academic Community and the Public at the Faculty of Medicine, Mitra Bunda Institute of Health Sciences - Sri Tati Rukiyani; Ditte Ayu Suntara; Dandy Citra; Tonny Yulianto; Yuli Mariany; Yanuarni Wulandari Baji Pamai; Sindy Nurafia; Rundito; Irbath Hamdanie; Farras Arlinda Rachmawati (Jurnal Pengabdian Masyarakat Bestari, 2026)
Human Papillomavirus (HPV) infection is a primary cause of cervical cancer, which remains a significant public health issue in Indonesia. Primary prevention efforts through HPV vaccination need to be continuously enhanced by engaging educational institutions as partners in health promotion. The activity was conducted from February 6–8, 2026, at the Faculty of Medicine, Mitra Bunda Health Institute, Batam, comprising stages of registration, health screening, education, vaccination, and observation for Adverse Events Following Immunization (AEFI). The target audience included students, the academic community, and the general public. A total of 400 participants registered, and 338 successfully received the HPV vaccine; no severe AEFIs were reported during the event. This program demonstrates that collaboration between educational institutions and healthcare professionals can support increased vaccination coverage and strengthen primary prevention efforts against cervical cancer through integrated education and healthcare services.